2016
DOI: 10.1161/circep.115.003721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and New Treatment Paradigm for Atrial Fibrillation

Abstract: Background Atrial fibrillation (AF) represents the most common arrhythmia leading to increased morbidity and mortality, yet, current treatment strategies have proven inadequate. Conventional treatment with antiarrhythmic drugs carries a high risk for proarrhythmias. The soluble epoxide hydrolase enzyme (sEH) catalyzes the hydrolysis of anti-inflammatory epoxy fatty acids including epoxyeicosatrienoic acids (EETs) from arachidonic acid to the corresponding pro-inflammatory diols. Therefore, the goal of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 42 publications
5
58
0
Order By: Relevance
“…In addition to pro‐inflammatory response, NF‐κB also plays an important role in cardiac hypertrophy, which may increase AF occurrence. Moreover, overexpression of Smad‐7 was also demonstrated to restrain NF‐κB‐driven cardiac inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pro‐inflammatory response, NF‐κB also plays an important role in cardiac hypertrophy, which may increase AF occurrence. Moreover, overexpression of Smad‐7 was also demonstrated to restrain NF‐κB‐driven cardiac inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…31 Pro-inflammatory cytokine levels were elevated with heart failure induced by TAC. 17 Therefore, to evaluate whether CYP2J2/EET counteracts the inflammatory response in AAC mice, we measured important pro-inflammatory cytokines and chemokines including TNF-α, IL-6 and MCP-1, and our data demonstrate the serum level of TNF-α, IL-6 and MCP-1 were significantly increased in mice with AAC ( Figure 5A). In contrast, treatment with AAV9-2J2 significantly decreased these cytokine levels.…”
Section: Cyp Epoxygenase 2j2 Inhibits Atrial Inflammations In Mice mentioning
confidence: 96%
“…Histological and western blot analyses of cardiac tissue were performed as we have previously described 9 . Genotyping analyses of Slc26a6 − / − mice are presented in Supplemental Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that lcPUFA epoxides are anti-inflammatory, anti-hypertensive, organ protective and analgesic. [2-9] Therefore, stabilization of lcPUFA epoxides in vivo through sEH inhibition is generally beneficial to human health and certain diseases, like chronic obstructive pulmonary diseases (COPD),[10, 11] atrial fibrillation[12] and diabetic neuropathic pain. [13-15].…”
Section: Introductionmentioning
confidence: 99%